THE DEBRIS DISTRIBUTION MODEL FOR REMOVAL PLANNING OF AN URBANIZED ESTUARINE COMPLEX - Barrella, Walter; Farraboti, Edineia; Carminatto, Amanda Aparecida; Adami, Fabiola Andrea Chofard; Rotundo, Matheus Marcos; Ramires, Milena; Júnior, Miguel Petrere (Quaestiones Geographicae, 2021)
We checked the spatial pattern of debris stranding at Praia de Santos (Brazil) in the first hour after the peak of high and low tide in summer and winter. We recorded and counted 20 types of debris (natural and anthropogenic) in 6 transects arranged in 3 zones along the beach (deposition, transport, and erosion). Canonical Correspondence Analysis (CCA) showed that buoyancy was an essential property in distinguishing debris stranding behaviours. The erosion zone, closer to the estuary showed that many mollusk shells, ropes and rocks, while plastics, styrofoam and fiber nylon were in the deposition zone. Throughout the estuary, we inspected the beach, identifying sections of origin and accumulation associated with the circulation system and currents. We propose the removal and recycling of debris from accumulation sites near highways and urban systems.